Perbandingan Tingkat Kepuasan Pelanggan Berdasarkan Segmentasi Usia Menggunakan Analisis ANOVA: Studi Kasus Pada Mie Gacoan - Nabilah Dwi Ananda; Karen Nibenia Hia; Nisa Azzahra; Elisa Maranatha Lumbantoruan; Rumsina Lubis; Sunita Dasman (GLOBAL SCIENTS PUBLISHER, 2026)
The culinary industry in Indonesia continues to grow rapidly alongside the increasingly modern lifestyle of its society. This study aims to determine whether there are differences in customer satisfaction levels at Mie Gacoan based on age segmentation. A quantitative comparative approach was used with One-Way ANOVA on 81 respondents divided into three age groups: 18–22, 23–27, and 28–35 years. The results indicate that there are significant differences in customer satisfaction across age groups, with the 18–22 age group showing the highest satisfaction level compared to the other groups.